2017
DOI: 10.1016/j.jcp.2016.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Finite element method for nonlinear Riesz space fractional diffusion equations on irregular domains

Abstract: In this paper, we consider two-dimensional Riesz space fractional diffusion equations with nonlinear source term on convex domains. Applying Galerkin finite element method in space and backward difference method in time, we present a fully discrete scheme to solve Riesz space fractional diffusion equations. Our breakthrough is developing an algorithm to form stiffness matrix on unstructured triangular meshes, which can help us to deal with space fractional terms on any convex domain. The stability and converge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…We choose α = β = 0.8 and τ = 10 −3 at t = 1 to observe the running time for different h. We observe that compared to the running time of FEM, CVM can reduce the running time significantly, which illustrates that CVM is more effective for solving the two-dimensional Riesz space fractional diffusion equation on convex domains. This is mainly due to the bilinear form in [41] that involves 8 fractional derivative terms and the approximation of two-fold multiple integrals, which are approximated by Gauss quadrature, while for CVM we only need to calculate 4 fractional derivative terms and the approximation of line integrals. We can see that the numerical solution is in excellent agreement with the exact solution, which demonstrates the effectiveness of our numerical method again.…”
Section: Discussion Of Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We choose α = β = 0.8 and τ = 10 −3 at t = 1 to observe the running time for different h. We observe that compared to the running time of FEM, CVM can reduce the running time significantly, which illustrates that CVM is more effective for solving the two-dimensional Riesz space fractional diffusion equation on convex domains. This is mainly due to the bilinear form in [41] that involves 8 fractional derivative terms and the approximation of two-fold multiple integrals, which are approximated by Gauss quadrature, while for CVM we only need to calculate 4 fractional derivative terms and the approximation of line integrals. We can see that the numerical solution is in excellent agreement with the exact solution, which demonstrates the effectiveness of our numerical method again.…”
Section: Discussion Of Numerical Resultsmentioning
confidence: 99%
“…Furthermore, according to the property of the stiffness matrix generated by the finite volume method, we chose a suitable sparse matrix format for the stiffness and utilised the Bi-CGSTAB iterative method to solve the linear system, which is more efficient than using Gauss elimination method. In addition, we made a comparison of our method with the finite element method proposed in [41], which demonstrated that our method can reduce CPU time significantly while retaining the same accuracy and approximation property as the finite element method. In future work, we shall investigate the unstructured mesh control volume method applied to other fractional problems on irregular convex domains, such as the twodimensional multi-term time-space fractional diffusion equation with variable coefficients or three-dimensional space fractional diffusion equations with variable coefficients.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations